Predictive factors for regional metastases in oral tongue squamous cell carcinoma - Anastasios Kanatas; Amy Marschall; Craig D. S. T. Needs; Thomas Mucke; James McCaul (Frontiers Media S.A., 2011)
The process of deciding to treat or not to treat the clinically N0 neck in early oral tongue carcinoma whether surgically or with radiotherapy remains difficult and open to discussion. This is due to the minority of patients who will have occult nodal metastases and the reduced outcome for those patients whose neck disease is not treated primarily. Studies which have looked at factors which may predict for nodal metastases both at the histological and immunohistochemical level and therefore help with this decision making process are reviewed.